2013
DOI: 10.1039/c3ra22999h
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-catalysed reaction for long-term fluorescent observation of single DNA molecules

Abstract: The technical development of long-term fluorescent observation of single DNA molecules is central to fields ranging from molecular biological detection to understanding the physical properties of them under a microscope. Here, we address this challenge using protocatechuic acid and protocatechuate-3,4dioxygenase (PADase) and demonstrate fluorescent lifetimes of dyed single DNA molecules of 150-180 s, three times longer than those without any treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…6). 69 One major drawback of previous studies was the need for fluorescence labeling, 75 which can affect the biomolecular characteristics. In our recent work, we aimed at label-free monitoring of biomolecular separation using the intensity variation of a laser diffracted using a nanopillar array, 70 and we demonstrated that our proposed nanopillars yielded label-free monitoring and separating of DNA molecules in a nonequilibrium manner.…”
Section: Dna Separation Using Nanopillars and Nanowallsmentioning
confidence: 99%
“…6). 69 One major drawback of previous studies was the need for fluorescence labeling, 75 which can affect the biomolecular characteristics. In our recent work, we aimed at label-free monitoring of biomolecular separation using the intensity variation of a laser diffracted using a nanopillar array, 70 and we demonstrated that our proposed nanopillars yielded label-free monitoring and separating of DNA molecules in a nonequilibrium manner.…”
Section: Dna Separation Using Nanopillars and Nanowallsmentioning
confidence: 99%